2011
DOI: 10.1111/j.1601-5037.2011.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Instability of self‐esteem, self‐confidence, self‐liking, self‐control, self‐competence and perfectionism: associations with oral health status and oral health‐related behaviours

Abstract: Our study showed that instability of self-esteem, self-confidence, self-competence, self-liking, self-control and perfectionism was associated not only with self-rated dental health but also with oral health behaviours. Understanding the psychological factors associated with oral hygiene can further the development and improvement in therapeutic strategies to be used in oral health-improving programs, as well as of programs aimed at prevention and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 44 publications
0
22
0
3
Order By: Relevance
“…Questions, which examined oral health-related behavior, were designed by the authors and took into consideration previously performed research on similar topics. [1][2][3] These questions included the frequency of tooth brushing, flossing, mouth rinsing, etc. The 10-question Fatigue Assessment Scale was used to investigate symptoms of fatigue.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Questions, which examined oral health-related behavior, were designed by the authors and took into consideration previously performed research on similar topics. [1][2][3] These questions included the frequency of tooth brushing, flossing, mouth rinsing, etc. The 10-question Fatigue Assessment Scale was used to investigate symptoms of fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…Studies suggest that individual oral hygiene correlates with emotions, physical and mental state. 1,2 A positive corelation was revealed between the sense of humor, self-esteem, self-confidence, self-love and the frequency of oral hygiene appliances usage. [1][2][3] Moreover, behavioral activity and fatigue were related to appropriate and infrequent oral health-related behaviors respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there seems to be no sound empirical evidence on the potential relationship of hypertension and self-rated teeth appearance, although a clinical study showed a potential linkage in patients with severe secondary hyperparathyroidism in chronic renal failure [9]. The linkage of poor mental health such as distress or depression and selfrated teeth appearance could be via the mechanism of low selfcompetence and appreciation [10].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 98%
“…It is unknown whether GBTs are associated with decrements in QOL. Studies of QOL associated with dental, orthodontic, and periodontal needs often focus on psychosocial well-being [33][34][35], but since QOL includes other dimensions that are unlikely to be affected by improvements to esthetics, notably physical functioning, it is unclear whether commonly-used measures of QOL would be able to capture improvements associated with treatment and therefore be meaningful assessment tools. Unlike more severe conditions, GBTs are unlikely to be associated with pain or difficulty eating, and probably have little to no impact on physical functioning.…”
Section: Patient Preference and Quality Of Life Advantagesmentioning
confidence: 99%